A Top-Down, Multi-Method and Multi-Scale Approach to Studying the Byzantine–Umayyad Settlement of Umm ar-Rasas (Amman, Jordan) - Marilena Cozzolino; Francesca Di Palma; Roberto Gabrielli; Paolo Mauriello; Giuseppe Scardozzi (Heritage)
The present study constitutes the latest in a series of investigations conducted between 2021 and 2023 as part of the ongoing, multidisciplinary research project at the UNESCO archaeological site of Umm ar-Rasas in Amman Governorate, Jordan, which began in 2013. Building on the foundations of previous studies, this latest research offers a comprehensive analysis of the region, with a special focus on pinpointing the boundaries of the Byzantine–Umayyad settlement. The delineation of these boundaries has hitherto been the subject of theoretical discourse only, thus rendering this study a significant addition to the field. An innovative multi-dimensional, multi-methodological, and multi-scalar approach has been adopted, incorporating the capabilities of remote sensing technologies, archaeological surveys, laser scans, and geophysical prospecting to facilitate a shared interpretation of the results. This approach has culminated in the establishment of a probable configuration of the northern limits, which is truly remarkable.